Predicting near-term, out-of-sample fish passage, guidance, and movement across diverse river environments by cognitively relating momentary behavioral decisions to multiscale memories of past hydrodynamic experiences - Goodwin, R. Andrew; Lai, Yong G.; Taflin, David E.; Smith, David L.; McQuirk, Jacob; Trang, Robert; Reeves, Ryan (Frontiers in Ecology and Evolution, 2023)
See Word or PDF file.